The evolving landscape of health and social care integration: in search of a unifying theory - Lee, Kheng Hock; Lee, Chien Earn (Frontiers in Medicine, 2025)
This paper explores the co-evolution of theoretical paradigms and care models within health and social care through the lens of complexity science. It argues that this co-evolution, characterized by a dynamic interplay between abstract principles and tangible practices, propels health systems toward greater human-centeredness and interconnectedness. Theories, acting as “attractors,” shape the landscape of possible care models, while the implementation and evaluation of these models, in turn, refine theoretical understanding. This continuous feedback loop, driven by emergent properties within the complex system of healthcare, fosters a dynamic evolution toward more holistic and effective care. The paper proposes a unifying framework to understand this ongoing process, emphasizing the interconnectedness of individual, community, and societal well-being. While further research is needed to validate this conceptual framework, it offers a valuable lens for analyzing historical trends and guiding future developments in health and social care.